Analysis of The Relationship of Rework and Inventory to Waste in The Ciputra Hospital Surabaya Project - Felicia Tria Nuciferani; Mukharom Dwi Anggara; Siti Choiriyah; Devi I Permatasari (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
The problem of material waste in construction projects will be difficult to avoid as it goes along with construction waste. One of the unavoidable problems in a construction project is repeating work or reworking. Rework will also affect the emergence of waste. In a series of construction project activities, inventory is always required to anticipate needs in the ongoing construction project process. Without an inventory, a construction project will encounter the risk that one day it will not be able to meet its needs. This research aimed to determine the correlation between rework and inventory to waste at the Ciputra Hospital Surabaya construction project. It employed a quantitative method by collecting data through a questionnaire distributed to 30 respondents in the project environment. Data analysis involved multiple linear regression analyzes and the SPSS 25 software program. The results of the t-test showed that rework partially had a positive effect on waste with a t-count value of 8.528, while inventory also had a positive effect on waste with a t-count value of 8.661. Simultaneous test results indicated that rework and inventory had a significant effect on waste, with an F-count value of 37.442. Keywords: Waste; Rework; Inventory